Election Commission of India: Institutionalising democratic uncertainties - Singh, Ujjwal Kumar; Roy, Anupama (New Delhi : Oxford University, 2019)
As the constitutional body that conducts elections, the Election Commission of India (ECI) has emerged as a trusted institution within the shared space of democracy in India. This process has, however, been a fraught one because of contestation over the ECIs constitutional responsibility and the power of Parliament to make laws to govern electoral matters.This comprehensive monograph discusses the history of the ECI through a study of the measures it has adopted to ensure certainty of procedures in order to maintain the democratic uncertainty of electoral outcome. In this context, innovations such as the Model Code of Conduct have enhanced the rule-making powers of the ECI. Going beyond the ECIs design and performance framework, Singh and Roy argue that changes in the nature of electoral contests and domination of political regimes have made the task of preserving electoral integrity and assuring its deliberative content a challenging one.
Keywords: Elections -- India; Elections; Politics and government